Nanofibre Electrospinning Poly(vinyl alcohol) and Cellulose Composite Mats Obtained by Use of a Cylindrical Electrode - Anna Sutka; Silvija Kukle; Janis Gravitis; Rimvydas Milašius; Jolanta Malašauskienė (Advances in Materials Science and Engineering)
A study of nanofibre composites obtained by electrospinning from poly(vinyl alcohol) (PVA) solutions of steam exploded hemp fibres and shives is reported. A combined treatment of steam explosion (SE), ball milling, and high-intensity ultrasound (HIUS) is applied to prepare cellulose nanofibres (CNF) from hemp fibres (CNF-F) and shives (CNF-S). The reflectance Fourier transform infrared (FTIR ATR) spectroscopy is used to analyze the obtained PVA/CNF composite mats. Morphology of the PVA/CNF composites was studied by scanning electron microscopy (SEM).